2017
DOI: 10.17509/ijal.v7i2.8357
|View full text |Cite
|
Sign up to set email alerts
|

Writing Introduction Sections of Research Articles in Applied Linguistics: Cross-Linguistic Study of Native and Non-Native Writers

Abstract: Genre studies allow researchers to observe the repeated communicative functions and their linguistic components in different genres (Brett, 1994). Writing the introduction section is a tough and burdensome task for both native and non-native speakers (Swales & Feak, 1994). Hence, the present study aimed to investigate the generic organization of English research article introductions written by native English and Iranian non-native speakers of English. A total of 160 published articles were selected from estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 19 publications
(30 reference statements)
7
32
0
1
Order By: Relevance
“…Step 3 Indicating RA structure Fig. 1 Creating a research space (CARS) model (Swales, 1990: 141) Almost all studies that have investigated the introduction section of RAs (e.g., Adika, 2014;Coker & Coker, 2012;Davies, 2014;Farnia & Barati, 2017;Zainudden & Shaari, 2017) employed the CARS model, either in its original state or modified form. The model has been found to be a viable tool for investigating rhetorical structures of academic writings.…”
Section: Move 1: Establishing a Territorymentioning
confidence: 99%
See 4 more Smart Citations
“…Step 3 Indicating RA structure Fig. 1 Creating a research space (CARS) model (Swales, 1990: 141) Almost all studies that have investigated the introduction section of RAs (e.g., Adika, 2014;Coker & Coker, 2012;Davies, 2014;Farnia & Barati, 2017;Zainudden & Shaari, 2017) employed the CARS model, either in its original state or modified form. The model has been found to be a viable tool for investigating rhetorical structures of academic writings.…”
Section: Move 1: Establishing a Territorymentioning
confidence: 99%
“…Philippines research introductions also showed extremely first choice utilisation of "Indicating a gap" strategy (Porras & Ingilan, 2017). In another jurisdiction, whereas Parsa and Tahririan (2017) reported that native speakers of Persian prefer "Indicating a gap" as their second-best choice in presenting the niche of their introductions, different studies found this same strategy as the writers" first choice (Farnia & Barati, 2017;Mahzari & Maftoon, 2007;Nimehchisalem et al, 2016). In Wuttisrisiriporn"s (2017) comparative study of Thai and American MA theses, "Indicating a gap" was the second-choice rhetorical strategy of the students.…”
Section: Related Studies On Establishing a Nichementioning
confidence: 99%
See 3 more Smart Citations